Analytical evaluation of elastic interaction in bolted flange joints. (August 2018) - Zhu, Linbo; Bouzid, Abdel-Hakim; Hong, Jun
Abstract: Bolted flange joints are the most popular type of connection of pressure vessels and piping equipment because of their ease of assembly and disassembly. However, the initial tightening of their bolts is a delicate operation because it is extremely difficult to achieve the target load and uniformity due to elastic interaction. This study consists of developing an analytical model to evaluate the elastic interaction of bolted flange joints subjected to multi-pass tightening patterns. The proposed analytical model is based on the theory of circular beams on elastic foundation. The parameters such as elastic compliance due to bending, twisting and bearing are involved to describe the effects of elastic interaction during the tightening sequence. The developed model based on the theory of circular beams on elastic foundation is compared to the straight beam on elastic foundation theory. The validity of the approach is supported by experimental tests conducted on a NPS 4 class 900 weld neck bolted flange joint and by finite element analysis on this bolted joint and a 52 heat exchanger flange joint using the criss-cross tightening and sequential patterns. This study provides an attractive alternative to evaluate the bolt tension scatter due to elastic interaction avoiding costly experimental tests and cumbersome FEA simulations. Highlights: An analytical model of elastic interaction in bolted flange joints is proposed. Elastic compliances are involved to describe the elastic interaction. The results of the analytical model, experiment and FEA are in good agreement. Tightening pattern and gasket stiffness have a significant effect on the elastic interaction.